Inhibition of 26S proteasome activity by α-synuclein is mediated by the proteasomal chaperone Rpn14/PAAF1 - Galka, Dajana; Ali, Tariq T.; Bast, Alexander; Niederleithinger, Marie; Gerhardt, Ellen; Motosugi, Ryo; Sakata, Eri; Knop, Michael; Outeiro, Tiago F.; Popova, Blagovesta; Braus, Gerhard H. (Aging cell, 2024)
Parkinson's disease (PD) is characterized by aggregation of α-synuclein (α-syn) into protein inclusions in degenerating brains. Increasing amounts of aggregated α-syn species indicate significant perturbation of cellular proteostasis. Altered proteostasis depends on α-syn protein levels and the impact of α-syn on other components of the proteostasis network. Budding yeast Saccharomyces cerevisiae was used as eukaryotic reference organism to study the consequences of α-syn expression on protein dynamics. To address this, we investigated the impact of overexpression of α-syn and S129A variant on the abundance and stability of most yeast proteins using a genome-wide yeast library and a tandem fluorescent protein timer (tFT) reporter as a measure for protein stability. This revealed that the stability of in total 377 cellular proteins was altered by α-syn expression, and that the impact on protein stability was significantly enhanced by phosphorylation at Ser129 (pS129). The proteasome assembly chaperone Rpn14 was identified as one of the top candidates for increased protein stability by expression of pS129 α-syn. Elevated levels of Rpn14 enhanced the growth inhibition by α-syn and the accumulation of ubiquitin conjugates in the cell. We found that Rpn14 interacts physically with α-syn and stabilizes pS129 α-syn. The expression of α-syn along with elevated levels of Rpn14 or its human counterpart PAAF1 reduced the proteasome activity in yeast and in human cells, supporting that pS129 α-syn negatively affects the 26S proteasome through Rpn14. This comprehensive study into the alternations of protein homeostasis highlights the critical role of the Rpn14/PAAF1 in α-syn-mediated proteasome dysfunction.
Zuerst veröffentlicht: 28. Februar 2024
Gesehen am 02.08.2024